Dynamics of laser-bumped electron–hole semiconductor plasma - Elgarawany, Amany Z.; Gamal, Yosr E. E.-D.; El-Hafeez, Samy A.; Moslem, Waleed M. (Frontiers in Physics, 2022)
Electron-hole pairs in semiconductor can be stimulated by laser beam with energy larger than the energy gap of the semiconductor. The interaction between an electron-hole plasma with laser beam can be a source of instability. The dependence of the instability on the electron and hole temperatures as well as the unperturbed potential of the incident laser are examined. Using Maxwell's equations along with electron-hole fluid equations, an evolution equation describes the system is obtained. The latter is reduced to an energy equation characterizes the localized pulses propagating.